Risk Factors and Clinical Characteristics of Metabolic Bone Disease of Prematurity - Mutlu, Mehmet; Aktürk-Acar, Filiz; Kader, Şebnem; Aslan, Yakup; Karagüzel, Gülay (American Journal of Perinatology, 2021)
Objective The study aimed to analyze the risk factors and clinical features of metabolic bone disease of prematurity (MBDP) in premature infants compared with infants of similar gestational age and birth weight without MBDP.Study Design This retrospective case–control study was performed by comparing 81 cases of MBDP with 63 controls to identify potential risk factors. Premature infants with a gestational age ≤33 weeks and birth weight <1,500 g were included. Medical records were examined in terms of maternal conditions, potential risk factors, and clinical characteristics.Results Bone fractures and invasive ventilator dependence were the most common clinical features of MBDP. Duration of invasive ventilation and total mechanical ventilation days, necrotizing enterocolitis, corticosteroid use, anticonvulsive drug use, duration of dexamethasone and caffeine use, total parenteral nutrition, and length of hospitalization were significantly higher in neonates with MBDP (p < 0.05). Breastfed neonates and those receiving human milk fortifier had a lower incidence of MBDP than those premature formula or mixed feeding (p < 0.05). Anticonvulsive drug use (odds ratio: 2.935; 95% confidence interval: 1.265–6.810) was identified as a risk factor for MBDP at multiple regression analysis.Conclusion Our results show that anticonvulsive drug use is a significant risk factor for the development of MBDP. If long-term use is not required, anticonvulsive drugs should be stopped as soon as possible. Further studies involving patients with MBDP are required to determine the risk factors and clinical features.Key Points
Keywords: metabolic bone disease; prematurity; risk factor